Crystallization and preliminary X-ray diffraction analysis of a new xyloglucanase from Xanthomonas campestris pv. campestris - de Araújo, Evandro Ares (International Union of Crystallography, 2013)

(untitled)
Xyloglucanases (Xghs) are important enzymes involved in xyloglucan modification and degradation. Xanthomonas campestris pv. campestris (Xcc) is a phytopathogenic bacterium which produces a large number of glycosyl hydrolases (GH), but has only one family 74 GH (Xcc-Xgh). This enzyme was overexpressed in Escherichia coli, purified and crystallized. Diffraction data sets were collected for the native enzyme and its complex with glucose to maximum resolutions of 2.0 and 2.1 Å, respectively. The data were indexed in a hexagonal crystal system with unit-cell parameters a = b = 153.4, c = 84.9 Å. As indicated by molecular-replacement solution, the crystals belonged to space group P6(1).